Options for Soil Health Measurement in Vineyards and Deciduous Fruit Orchards, with Special Reference to Nematodes - Kapp, C.; Storey, S.G.; Malan, A.P. (South African Journal of Enology and Viticulture, 2013)
Soil is a non-renewable resource and supports all land-based forms of life. The sustainable production of crops is becoming progressively more critical as human populations increase and viable agricultural land decreases. Soil health plays an indispensable part in the sustainability of soil as a resource for future generations. For this very reason it is important to have suitable tools to measure the improvement or deterioration of soil health in vineyards and orchards. In this review, the use of different bio-indicators to indicate soil health will be discussed, with special emphasis on the use of nematode population structure and function as indicators of soil health. The use of nematodes as a bio-indicator of soil health can play a crucial role in the establishment of future sustainable production of grapes and fruit in the Western Cape. This paper provides a comprehensive review of soil health, the use of different biological indicators, and the potential of nematodes as suitable indicators thereof, aimed at vineyards and deciduous fruit orchards.